Analysis of related gene of the HLA system class I in women with cervical intraepithelial neoplasia grades II and III - Xavier, Marina Barbara de Souza (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Objective: To evaluate the HLA-C gene in the progression and regression of cervical lesions caused by HPV infection, the present study aimed to analyze the genetic diversity and allelic variants of HLA-C gene in women CIN 2 and CIN 3 diagnosed, comparing with those without abnormalities on cervical cytology with and without the presence of infection HPV. Materials and Methods: The study group consisted of 84 women with CIN 2 and 90 women with CIN 3; the control group had no abnormality in cervical cytology consisted of 102 women negative for the presence of the HPV and 76 women with positive HPV infection. Samples were obtained from the metropolitan region of Curitiba-PR, Brazil, aged between 15 and 45 years old. The study group was treated in the Department of Pathology of the Cervical Erasto Gaertner Hospital, Curitiba and the control group was recruited in cervical cancer prevention campaigns promoted by public entities in association with the Department of Obstetrics and Gynecology, Hospital de Clínicas, Federal University of Parana and Histocompatibility and Immunogenetics Laboratory, Department of Genetics, UFPR. The HPV detection was performed by the Hybrid Capture 2 (CH2®) methodology. The DNA was extracted from peripheral blood samples and HLA-C genotyping was performed PCR-SSOP method. Results: Using G test it was observed that alleles HLA-C* 05:01 (p = 0.0096), HLA-C * 07:01P (p = 0.0096), HLA-C*07:02 (p = 0.0024), HLA-C*12:03 (p = 0.0010), HLA-C*15:02P (p = 0.0176) and HLAC*16:01 (p = 0.0415) were significantly more frequent in the study. The homozygous genotype HLAC*04:01P/*04:01P was the most frequent, reflecting the high frequency in the population studied. Allelic variants HLA-C*05:01 (p = 0.009; OR = 4.57; 95%CI 0.5749 – 36.3774), HLA-C*07:02 (p = 0.002; OR = 11.42; 95%CI 1.5173 – 86.2209) and HLA-C*12:03 (p = 0.001; OR = 7.59; 95%CI 0.9886 – 58.3472) were more frequent in women with CIN than in women with no cytological abnormalities, positive for the presence of HPV. The presence of the HLA-C*07:02 suggests susceptibility to progression of cervical intraepithelial lesion. Conclusion: Additional studies should be conducted to assess the significance of the risk of developing CC, especially in the context of KIR ligand HLA-C interactions in order to evaluate the interaction of immune system with the development of cervical cancer response.